An investigation of the effectiveness of the framing systems in steel structures subjected to blast loading - Coffield, Amy; Adeli, Hojjat (Journal of Civil Engineering and Management, 2014)
The effectiveness of different framing systems for three seismically designed steel frame structures subjected to blast loading is investigated. The three faming systems considered are: a moment resisting frame (MRF), a concentrically braced frame (CBF) and an eccentrically braced frame (EBF). The blast loads are assumed to be unconfined, free air burst detonated 15 ft (4.572 m) from one of the center columns. The structures are modeled and analyzed using the Applied Element Method, which allows the structure to be evaluated during and through failure. Failure modes are investigated through a plastic hinge analysis and member failure comparison. Also, a global response analysis is observed through comparison of roof deflections and accelerations. A conclusion of this research is that braced frames provide a higher level of resistance to the blast loading scenario investigated in this research. Both the CBF and EBF had a smaller number of failed members and plastic hinges compared to the MRF. They also had smaller roof deflection and acceleration. The CBF yielded the fewest number of plastic hinges but the EBF had a slightly fewer number of failed members.